Analisis Efektivitas Pembelajaran Geografi pada Pelaksanaan Tatap Muka Terbatas (TMT) di SMA se-Kecamatan Taman Sari Jakarta Barat - Fellix Rimba (Sosio-Didaktika: Social Science Education Journal, 2023)
This study aims to determine the implementation of geography learning during the pandemic and the effectiveness of geography learning in senior high schools throughout the Taman Sari sub-district, West Jakarta. This research is located in Senior high school in Taman Sari, West Jakarta, which consists of 5 schools namely, SMAN 17 West Jakarta, SMA Sentosa Pagi, SMAN 2 Jakarta, SMA Santo Leo and Ricci School. The data collection techniques used in this study were observation techniques, documentation studies and interview techniques. The analytical technique used in this research is descriptive qualitative analysis, which is to explain the analysis of the effectiveness of geography learning in the implementation of limited face-to-face learning in class X IPS SMA in Taman Sari, West Jakarta. Which will be presented in the form of percentages, tables, graphs, images and others. The results showed that (1) the implementation of learning in high schools throughout the Taman Sari District during the covid-19 pandemic was carried out face-to-face limited and online by using the whatsapp group application, google classroom and zoom meeting. (2) the effectiveness of learning geography in the face-to-face period is limited, judging from the quality of learning that is classified as quite effective with a score of 76.22%, the level of teaching is quite effective with a score of 78.37%, incentives are categorized as quite effective with a score of 68.90% and learning time is in the category of quite effective with a score of 90% Learning geography in face-to-face limited shows quite effective results, which is equal to 78.37%.Keywords:  Learning Effectiveness, Limited Face-to-face